Faktor organisasional dan perilaku sebagai determinasi kecurangan akuntansi di Pemerintah Desa - Elsa Arum Prafita Sari; Siti Aliyah (LPMP Imperium, 2025)
This study analyzes the influence of organizational and behavioral factors on accounting fraud within Indonesian village governments. Using a quantitative approach, primary data were collected via questionnaires from 141 village officials across 11 villages (saturated sampling). Multiple linear regression analysis in SPSS 25 revealed that among five independent variables, only unethical behavior had a positive, significant influence on accounting fraud. Other variables—internal control, organizational ethical culture, compensation suitability, and organizational commitment—did not show a significant effect. These findings indicate that fraud is driven more by individual behavior than systemic factors. The study recommends strengthening individual integrity through ongoing ethics training and tightening oversight mechanisms. It contributes to understanding the determinants of fraud at the village level, with policy implications for embedding ethical values and implementing behavior-focused prevention programs. Public interest statements This study helps the public understand that unethical behavior is the leading cause of financial fraud in village governments. Hence, communities can actively promote transparency, accountability, and oversight of village funds to support shared welfare.